Development of a half-meter scale Traveling-Wave (TW) SRF cavity - Furuta Fumio; Kazakov Sergey; Khabiboulline Timergali; McGee Kellen; Ng Trista; Yakovlev Vyacheslav (EPJ Web of Conferences, 2024)
Traveling-wave (TW) technology can push the accelerator field gradient of niobium SRF cavity to 70 MV/m or higher beyond the fundamental limit of 50~60 MV/m in Standing-Wave regime. The 1st demonstration of TW resonance excitation in a proof-of-principle 3-cell SRF cavity in 2 K liquid helium was successfully carried out at Fermilab in collaboration with Euclid Techlabs [1]. In parallel with that, the RF design process of 0.5~1 meter scale TW cavity was begun at Fermilab for advancing TW technologies necessary more for future accelerator-scale one. Considering the physical dimensions of existing SRF facilities (for fabrication, processing, and cryogenic testing) and the lessons learned from the 3-cell, Fermilab has proposed a preliminary RF design of a half-meter scale TW SRF cavity [2]. It consists of a 7-cell structure and a power feedback waveguide (WG) loop with new RF configurations to control TW resonance. Here we report a preliminary RF design, development plans, and activities toward a TW 7-cel SRF cavity.